Concurrent mitomycin C, 5-fluorouracil, and radiotherapy in the treatment of locally advanced carcinoma of the cervix: A randomized trial - Lorvidhaya V. (2014)
Purpose: This is a prospective, Phase III multicenter randomized trial to assess the effectiveness of concurrent intravenous mitomycin C, oral 5-fluorouracil (5-FU), and radiotherapy (RT) in locally advanced carcinoma of the cervix. Methods and Materials: Between January 1988 and November 1994, 926 patients with locally advanced carcinoma of the cervix, FIGO Stage IIB-IVA, were entered into this study. The patients were randomized into four arms, as follows: Arm 1: conventional RT; Arm 2: conventional RT and adjuvant chemotherapy; Arm 3: conventional RT plus concurrent chemotherapy; Arm 4: conventional RT plus concurrent chemotherapy and adjuvant chemotherapy. Concurrent chemotherapy consisting of intravenous mitomycin C at 10 mg/m2 was given on Days 1 and 29, and oral 5-FU at 300 mg/day was administered on Days 1-14 and 29-42 during RT. Adjuvant chemotherapy of 5-FU orally at 200 mg/day was given for three courses of 4 weeks, with a 2-week rest every 6 weeks. Six centers participated in the trial. Results: The median follow-up time was 89 months. Acute side effects were generally higher in concurrent arms, but most of the patients tolerated the treatment well. Bone marrow toxicity was also higher in concurrent arms. The 5-year actuarial disease-free survival (DFS) was 48.2%, 54.1%, 64.5%, and 59.7% for arms 1, 2, 3, and 4, respectively. The pattern of failure revealed a significant increase in locoregional recurrence in the nonconcurrent chemoradiotherapy arm. The local recurrence was 25.5%, 20.6%, 14.3%, and 17.6% for arms 1, 2, 3, and 4, respectively. The metastatic rates were not significantly different in all four arms. At the time of analysis, there were no increases in late side effects, especially in gastrointestinal and genitourinary systems. Conclusions: Concurrent chemotherapy, mitomycin C, and 5-FU together with conventional RT showed an improved DFS rate when compared with conventional RT alone in patients with locally advanced carcinoma of the cervix. © 2003 Elsevier Science Inc.